A preliminary study of the morphological variation of rhizomes in Zingiber Mill. and its role in taxonomy - Bai, Lin; Xia, Nian‑He (Phytotaxa, 2024)
The rhizomes of Zingiber are highly diverse and have potential in taxonomy, but their fundamental structure has never been properly understood in connection with an understanding of the sympodial growth form of the whole plant. This study is based on a literature review and on observations of fresh materials of 32 Zingiber species mainly from China, representing all four sections of the genus. An analysis of the sympodial modular growth habit of these plants has recognised that both isomodular and heteromodular growth exist within the genus. The study shows that rhizomes of Zingiber are highly-organised, compound, sympodial structures. By introducing the term rhizome unit, Zingiber rhizomes can be meaningfully described by depicting the morphology of the rhizome units and the relative arrangement of these units to one another. Six morphological attributes of rhizome units (shape, size, direction of growth, colour and number of nodes per rhizome, and length of internodes) and two attributes of their relative arrangement to one another (dorsiventral vs lateral position of rhizome units and the ramification position along the length of rhizome unit) are discussed. A preliminary assessment of variation patterns and the taxonomic value of these characters are presented. Together, these attributes contribute to the overall morphology of rhizomes. The relationship between rhizome structure and the above-ground clumping habit is discussed. The term pseudo-neck is coined to refer to the narrowed basal part that occurs in the rhizome units of some Zingiber species while the thick apical part of rhizome units where the internodes are often shorter than those on the pseudo-neck is called head. Problems with existing terminology for rhizome and plant habit descriptions in Zingiber are highlighted. This study suggests that whether the plane of distichy of leaves is parallel or perpendicular to the rhizome unit, a key character that many previous studies used for subdivision of Zingiberaceae, needs re-assessment, because in Zingiber both states of the character exist. Characters of rhizome morphology of the four sections in Zingiber are discussed, but studies of a larger number of species are needed to better-assess the relevance of these characters to the infrageneric classification of the genus. Schematic illustrations and colour plates of rhizomes from representative species are provided to assist the descriptions and discussions. It is hoped that this preliminary study will facilitate and encourage more comprehensive studies of rhizomes of Zingiber and of other genera within Zingiberaceae. Such work will lead to a better understanding of these structures and help establish a more comprehensive and accurate terminology for them, which in turn will facilitate the taxonomy and identification of the family.